Penyuluhan Strategi Mengatasi Skabiesis Melalui Identifikasi Sarcoptes Scabiei Pada Kasur Santri Pondok Pesantren Tabiyatul Banin Kecamatan Sumber Kabupaten Cirebon - Solikhah Solikhah; Pipin Supenah; Muhammad Ibnu Ubaidillah; Usdiyanto Usdiyanto; Oktafirani Al Sas; Rizal Ibrahim Aji; Muhammad Azhari (BADAN PENERBIT STIEPARI PRESS, 2023)
Health is very important for human life. Health can be expressed in two senses, especially in the narrow and broad sense. Skin health problems are something that needs to be considered by the community because skin health is still a matter of little concern in terms of personal and environmental hygiene, one of which is scabies. Scabies is caused by the mite Sarcoptes scabiei var hominis,s. This disease usually affects humans who live in groups and live together, such as in dormitories. This study aims to determine the presence of Sarcoptes scabiei on the mattresses of students at the Tarbiyatul Banin Islamic boarding school and to determine the percentage of mattresses that contain Sarcoptes scabiei at the Tarbiyatul Banin Islamic boarding school. Descriptive research methods and inspection methods using microscopic methods. For data analysis using the frequency descriptive statistics SPSS program. The results of the 35 samples of mattress dust examined were 4 positive samples with a percentage of 11.4%, while 31 samples of mattress dust were negative with a percentage of 88.6%.